ANALYSIS OF USING EFFICIENT LOGGING TOOLS AT PT. PURWA PERMAI IN CENTRAL KALIMANTAN - Sona Suhartana; Yuniawati Yuniawati (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2008)
A high log demand that often exceeds its supply capability should be overcome by using appropriate logging tools. Numerous kinds and types of logging tools require a well planning in their utilization. Number of tools which are greater or fewer than what is actually needed can be disadvantageous for a company. In relevant to these aspects, a study was carried out at a timber estate in Central Kalimantan in 2007. The aim of the study was to find out an efficient number of tools used for logging in a timber estate. The analysis was based on the target and realization of the company’s log production. The result revealed that: (1) Optimum number of logging tools depended on production target, i.e. 41 units of chainsaws for felling, 42 units of farm tractors for skidding, 9 units of loaders for loading and unloading, and 36 units of trucks for transportation; (2) Number of logging tools as obtained from all activities in the field was fewer than that from the analysis based on production target and realization. This condition indicated that number of logging tools used in the company was not yet efficient.